Safety pharmacology in pharmaceutical development approval and post marketing surveillance - Gad, Shayne C. 1948- (CRC Press, 2012)
"This book covers the regulatory required evaluation and study of the potentially adverse pharmacological effects of new drugs, from the general regulatory requirements to the specific studies that must be done and how they are performed and interpreted. Based on more than 30 years of direct experience, the author describes tricks and practical insights for making studies work and understanding why they don't. The second edition includes current regulations (US FDA and international especially Europe and Japan) and updated test methods, interpretation, and science"--Provided by publisher.